2020
DOI: 10.1136/bmjopen-2019-035302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on pain and physical function in patients with knee osteoarthritis (OA): an OA Trial Bank protocol for a systematic review and individual patient data (IPD) meta-analysis

Abstract: IntroductionObservational data suggest that vitamin D deficiency is associated with the onset and progression of knee osteoarthritis (OA). However, randomised controlled trials (RCTs) to date investigating the efficacy of vitamin D supplementation in knee OA have reported conflicting results. Further research is needed to clarify the effects of vitamin D on patient-reported outcomes and determine whether there are patient subgroups who may benefit from the supplementation. The aim of this individual patient da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…To the best of our knowledge, we provide here the first quasi-experimental data of patients with musculoskeletal pain examining the effect of vitamin D supplementation in addition to physiotherapy compared to only physiotherapy intervention on the reduction of pain parameters (e.g., pain severity, affective pain interference, and physical pain interference). In line with our findings, a systematic review and meta-analysis of published randomized controlled trials suggested that vitamin D supplementation can decrease pain scores significantly ( 31 ). Another review also concluded that vitamin D may establish a safe, simple, and potentially beneficial way to reduce pain among patients with vitamin D deficiency ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, we provide here the first quasi-experimental data of patients with musculoskeletal pain examining the effect of vitamin D supplementation in addition to physiotherapy compared to only physiotherapy intervention on the reduction of pain parameters (e.g., pain severity, affective pain interference, and physical pain interference). In line with our findings, a systematic review and meta-analysis of published randomized controlled trials suggested that vitamin D supplementation can decrease pain scores significantly ( 31 ). Another review also concluded that vitamin D may establish a safe, simple, and potentially beneficial way to reduce pain among patients with vitamin D deficiency ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…Vitamin D reduced pain and improved function in knee OA patients. While deficiency in endogenous vitamin D, reflected by low levels of circulating 25 OH vitamin D, was associated with the onset and progression of knee OA [38], maybe through an increased frequency of medial meniscus lesions [39], results of individual RCTs were inconclusive [40][41][42][43]. Their outcomes varied from a non-significant trend for symptom reduction [40][41][42] to a small but statistically significant benefit on pain and function after 12 months of administration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their analysis, the authors conclude that despite the fact vitamin D supplementation may improve pain and function in patients with knee osteoarthritis, the evidence from randomized clinical trials (RCTs) was controversial, because not all the RCTs measured the potential moderators of interest, or, not all of them were measured in the same way. Nevertheless, the results published by Jin et al can provide critical evidence to help clinicians make subgroup-specific treatment decisions in order to increase therapeutic efficacy [ 59 ].…”
Section: Vitamin D and Pain Managementmentioning
confidence: 99%